SURVIVAL OF PLANTS SPECIES IN SEASONALLY FLOODED FORESTS OF THE PERUVIAN AMAZONIA - FLORES LLAMPAZO, Gerardo Rafael (2023)
The survival of species in a seasonally flooded forest leads to a better understanding of strategies for conservation and ecological restoration. This paper reports species tolerant to flooded areas by evaluating the survival of species planted for forest restoration. Of the seventeen species studied, five showed high potential for use in seasonally flooded forest restoration. In general, the species P. munguba, C. tapia, H. crepitans, S. reticulata and M. dubia had a survival rate higher than 50%. S. reticulata had the highest survival with 91,1% in non‑submergence conditions. However, C. tapia (65,6%) and M. dubia (52,8%) tolerated greater submergence. The survival of plants is directly related to characteristics of adaptation to periods and levels of flooding, which is also conditioned by the heterogeneous microtopography of Amazonian flooded forests.